Novel Heme Oxygenase-1 Inducers Palliate Inflammatory Pain and Emotional Disorders by Regulating NLRP3 Inflammasome and Activating the Antioxidant Pathway - Montse Pérez-Fernández; Irene Suárez-Rojas; Xue Bai; Ignacio Martínez-Martel; Valeria Ciaffaglione; Valeria Pittalà; Loredana Salerno; Olga Pol (Antioxidants, 2023)
Chronic pain caused by persistent inflammation is current in multiple diseases and has a strong negative impact on society. It is commonly associated with several mental illnesses, which can exert a negative influence on pain perception, and needs to be eradicated. Nevertheless, actual therapies are not sufficiently safe and effective. Recent reports demonstrate that the induction of heme oxygenase-1 (HO-1) enzyme produces analgesic effects in animals with osteoarthritis pain and reverses the grip strength loss caused by sciatic nerve crush. In this research, we evaluated the potential use of three new HO-1 inducers, 1m, 1a, and 1b, as well as dimethyl fumarate (DMF), for treating persistent inflammatory pain induced by the subplantar injection of complete Freud’s adjuvant and the functional deficits and emotional sickness associated. The modulator role of these treatments on the inflammatory and antioxidant pathways were also assessed. Our findings revealed that repeated treatment, for four days, with 1m, 1a, 1b, or DMF inhibited inflammatory pain, reversed grip strength deficits, and reversed the linked anxious- and depressive-like behaviors, with 1m being the most effective. These treatments also suppressed the up-regulation of the inflammasome NLRP3 and activated the expression of the Nrf2 transcription factor and the HO-1 and superoxide dismutase 1 enzymes in the paw and/or amygdala, thus revealing the anti-inflammatory and antioxidant capacity of these compounds during inflammatory pain. Results suggest the use of 1m, 1a, 1b, and DMF, particularly 1m, as promising therapies for inflammatory pain and the accompanying functional disabilities and emotional diseases.